A descriptive study of 36 cases of solitary soft tissue cysticercosis at Ramathibodi hospital from surgical specimens during 1990-2006 - Vorachai Sirikulchayanonta (2018)
We present a study of 36 cases of solitary soft tissue cysticercosis retrieved from pathological reports and medical records during 1990-2006. The soft tissue was the most common organ affected by cysticercosis in our study accounting for 75% of all affected cases. The brain was the second most common, and accounted for 15%. The most common location for the soft tissue lesions was upper extremities which accounted for 33% of cases, and the least common sites were the back, eyelid, buttock and cheek, which accounted for 3% each. Preoperative diagnoses of the lesions were as follows: lipoma, masses of undetermined nature, cysts, abscesses, fat necrosis and lymphadenitis. The mean size of lesions was 1.5 cm; the minimum and maximum sizes were 0.3 and 3 cm, respectively. The mean age of the patients was 33.5 years and the range was 9 to 68 years. The ratio of males to females was 1 to 5, which may reflect differences in eating habits and social life between males and females in our society. Our findings indicated that none of the cases in our study were diagnosed as cysticercosis preoperatively. Therefore, clinicians should include cysticercosis in the differential diagnosis of soft tissue cystic nodules or masses. Data regarding the sizes of lesions should be helpful in differentiating this entity from other soft tissue lesions in clinical practice and on magnetic resonance imaging.